Inducing Partner Preference in Mice by Chemogenetic Stimulation of CA2 Hippocampal Subfield - Cymerblit-Sabba, Adi; Smith, Adam S.; Williams Avram, Sarah K.; Stackmann, Michelle; Korgan, Austin C.; Tickerhoof, Maria C.; Young, W. Scott (Frontiers in Molecular Neuroscience, 2020)
Social recognition is fundamental for social decision making and the establishment of long-lasting affiliated behaviors in behaviorally complex social groups. It is a critical step in establishing a selective preference for a social partner or group member. C57BL/6J lab mice do not form monogamous relationships, and typically do not show prolonged social preferences for familiar mice. The CA2 hippocampal subfield plays a crucial role in social memory and optogenetic stimulation of inputs to the dorsal CA2 field during a short memory acquisition period can enhance and extend social memories in mice. Here, by chemogenetic direct stimulation of the monosynaptic projections from the hypothalamic paraventricular nucleus (PVN) to the CA2 during the cohabitation period, we show that partner preference in mice can be induced. Specifically, male mice spend more time in social contact, grooming and huddling with the partner compared to a novel female. Preference was not induced by prolonging the cohabitation period and allowing more time for social interactions and for males to sire pups with the familiar female. These results suggest that PVN-CA2 projections are part of an evolutionarily conserved neural circuitry underlying the formation of social preference and may promote behavioral changes with appropriate stimulation.